Left ventricular mass and cardiac function in a population of children with chronic kidney disease - Mencarelli, Francesca; Fabi, Marianna; Corazzi, Valentina; Doyon, Anke; Masetti, Riccardo; Bonetti, Simone; Castiglioni, Laura; Pession, Andrea; Montini, Giovanni (Pediatric nephrology, 2014)
Cardiovascular disease (CVD) is a common cause of morbidity and mortality in children with chronic kidney disease (CKD). Left ventricular hypertrophy (LVH) and diastolic dysfunction (LVDD) are early markers. The aims of this study were to evaluate (1) LVH and LVDD, using both conventional echocardiographic evaluation and Tissue Doppler Imaging (TDI), and (2) the correlation between cardiac disease and possible risk factors, in children with CKD.
Gesehen am 14.09.2020
First published: 15 December 2013